Sistem Informasi Audit Mutu Internal Universitas Islam Negeri Sultan Syarif Kasim Riau (Studi Kasus: Lembaga Penjaminan Mutu) - Novi Yanti (Sosial Budaya, 2013)
Evaluation of the implementation of the Internal Quality Assurance System (SPMI) in college has been implemented by a working group within the Directorate of Academic. State Islamic University implementation of internal audit college. State Islamic University of Sultan Syarif Kasim Riau has conducted in each department/study program. Along with the development of State Islamic University of Sultan Syarif of science. It is appropriate this problem is mitigated by the use of information systems. Information systems are built is designed to assist, facilitate and streamline the work performed by an auditor and auditee in the that apply, as well as facilitate the department/study program in the administration and academic evaluation system. The system is built to be used by auditors and users (auditee)